2001
DOI: 10.1007/bf02443575
|View full text |Cite
|
Sign up to set email alerts
|

Induction of caspase-8 in human cells by the extracellular administration of peptides containing a C-terminal SLV sequence

Abstract: SummaryExtracellular administration of a membrane permeable model peptide containing the tripeptide sequence, SLV, at the C-terminus to human endothelial and kidney cells resulted in an induction of caspase-8 (FLICE), the apical enzyme of the apoptosis cascade. The unmodified or N-terminally SLV-tagged peptide had no effect, thereby eliminating an unspecific induction of apoptosis as the cause of the caspase activity observed. Drastic alterations of primary structure and structure forming properties of the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Externally administered KLA-peptide bearing the tripeptide SLV Cterminally is able to specifically activate caspase 8. The specificity is indicated by the inactivity of the components alone and of the KLA-conjugate bearing the SLV-sequence N-terminally (Scheller et al, 2001). Replacement of the KLA-peptide by the Antennapedia sequence resulted in similar biological activity.…”
Section: Substance P Rapidly Translocates Through the Plasma Membranementioning
confidence: 99%
“…Externally administered KLA-peptide bearing the tripeptide SLV Cterminally is able to specifically activate caspase 8. The specificity is indicated by the inactivity of the components alone and of the KLA-conjugate bearing the SLV-sequence N-terminally (Scheller et al, 2001). Replacement of the KLA-peptide by the Antennapedia sequence resulted in similar biological activity.…”
Section: Substance P Rapidly Translocates Through the Plasma Membranementioning
confidence: 99%
“…MAP (named after “model amphipathic peptide”) is an artificial CPP that integrates both hydrophobic and hydrophilic residues in opposite sides of its α-helical structure, resulting in a very well-defined amphipathic α-helix [ 13 ]. This CPP, whose sequence is KLALKLALKALKAALKLA, has the ability to translocate a variety of compounds such as oligonucleotides [ 14 ], peptides [ 15 ], and small proteins (like cytochrome c) across cell membranes [ 16 ]. Moreover, in a study by Hällbrink et al, addressing the cellular uptake kinetics of several CPP, MAP was found to display the fastest cellular uptake, along with the ability to induce leakage by disturbing the membrane integrity at concentrations as low as 1 μM [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Replacement of the KLA-peptide by penetratin resulted in similar biological activity. 240 In a comparative study Hällbrink et al have demonstrated that peptide KLALKLALKALKAALKLA and its conjugate with a model pentapeptide cargo are taken up more efficiently and quickly by Bowes human melanoma cells than similar pentamer construct of other cell penetrating peptides like transportan, Tat (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), or penetratin. 75 The uptake of antisense ODNs by mammalian cells (calf aortic endothelial cells, CHO cells) was compared with that of their respective conjugates or complexes with cationic KLA peptides (KLALKLALKALKAALKLA, KALKLKLAALALLKLKLA, KLGLKLGLKGLKGGLKLG, KGLKLKGGLGLLGKLKLG) of varying helix-forming propensity and amphipathicity and with penetratin.…”
Section: Kla Model Peptidesmentioning
confidence: 99%